STUDY ON THE FITNESS OF THE PUPILS FROM THE SECONDARY SCHOOL (8TH GRADE) FROM THE SCHOOL OF IPOTEŞTI (SUCEAVA COUNTY) - Leuciuc F. V. (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2013)
The aim of this study is to evaluate the fitness of the pupils based on the motrical activities used in the physical education lesson.If we can determinate the fitness level of the pupils from the secondary school (8th grade, there could be choosen the methods and exercices which ensure an optimal dosage of the physical effort's parameters during the physical education lessons in order to achieve the specific objectives of this discipline. The obtained results indicate the need to allocate a greater number of physical education hours per week in order to improve the results in control tests from assessment system of secondary school, where subjects' performances were medium, but also to effectively contribute to the achievement of specific objectives.